An Enemy of the People - Ibsen, Henrik, 1828-1906; Sharp, R. Farquharson (Robert Farquharson), 1864-1945 (Salt Lake City, UT : Project Gutenberg, 2000)
"An Enemy of the People" by Henrik Ibsen is a play written in 1882 that explores the clash between truth and societal pressure. Dr. Thomas Stockmann discovers dangerous contamination in his town's new spa baths and decides to expose the threat to public health. His decision triggers fierce opposition from local leaders, including his own brother, who fear economic ruin. As the community turns against him, Stockmann faces professional and personal consequences for challenging the establishment and refusing to compromise his principles. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/An_Enemy_of_the_People
Release date is 2000-12-01
Produced by Martin Adamson. HTML version by Al Haines.
Keywords: Social conflict -- Drama; Physicians -- Drama; Norwegian drama -- Translations into English; Springs -- Drama; Pollution -- Drama